GaAs PHEMT single-ended mixers for 28 GHz applications - Rahman, Nuriha Abd; Majlis, Burhanuddin Yeop (Penerbit Universiti Sains Malaysia, 2004)
Mixers are key devices for front-end components in any transceiver of a communication system. The performance of a receiver rely heavily on the mixer operation in terms of its conversion loss (gain), noise figure, port-to-port isolation, intermodulation distortion and dynamic range. Microwave mixer can be designed by using Schottkybarrier diode or FET, either MESFET or HEMT. Using a FET rather than a diode as the non-linear element in a mixer has several advantages. Some of these include the possibility of achieving a conversion gain, using lower LO drive power and obtaining isolation between the signal ports of the FET